2019
DOI: 10.1080/09583157.2019.1675144
|View full text |Cite
|
Sign up to set email alerts
|

The host range and impact of Aceria angustifoliae (Eriophyidae), a potential biological control agent against Russian olive, Elaeagnus angustifoliae (Elaeagnaceae) in North America

Abstract: Russian Olive, Elaeagnus angustifolia was introduced into North America primarily as a wind break and shade tree. Today it is listed as a noxious weed in the U.S. and Canada. During field surveys in the native range, the eriophyid mite, Aceria angustifoliae was identified as a promising biological control agent. Results from no-choice and open-field tests suggest that this is a highly specialized herbivore and that the risk to non-target plants in North America is negligible. The impact study revealed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This species appeared in the Western USA and Canada without intentional introduction and now it is considered as potential regulator of Cytisus (Pratt et al 2019 ). Release of Aceria angustifoliae against Elaeagnus angustifolia (Russian olive) is being considered in the USA and Canada (Weyl et al 2019 ; Weyl and Humair 2022 ). In spring 2022, the Canadian Food Inspection Agency (CFIA) approved field release of the mite in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…This species appeared in the Western USA and Canada without intentional introduction and now it is considered as potential regulator of Cytisus (Pratt et al 2019 ). Release of Aceria angustifoliae against Elaeagnus angustifolia (Russian olive) is being considered in the USA and Canada (Weyl et al 2019 ; Weyl and Humair 2022 ). In spring 2022, the Canadian Food Inspection Agency (CFIA) approved field release of the mite in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…B 376: 20200383 olive (Elaeagnus angustifolia) was introduced from Eurasia into the northern Rocky Mountain region of North America for windbreaks, where it has become an aggressive invader of riparian areas, outcompeting native tree species and changing hydrologic processes [89]. In order to reduce the invasiveness of Russian olive without harming Russian olive stands still used as windbreaks, efforts have been made to develop biological control agents that consume a substantial proportion of its seeds [90]. However, because Russian olive has a crop failure roughly every fifth year [10], predator satiation could reduce the efficacy of these agents by limiting the overall number of seeds they consume.…”
Section: (E) Application 5: Biological Control Of Plants Using Seed Predatorsmentioning
confidence: 99%
“…Field studies through observations and experiments have shown not only massive reductions in seed set of individual plants (e.g., 66% by A. angustifoliae against Russian olive [121], to 95% by A. alhagi against camelthorn [70], and up to 98% by A. acroptiloni against Russian knapweed [122]), but also, impressive reductions in biomass (e.g., 66% reduction in size of Russian thistle by A. salsolae [89] and a 49% reduction in above ground Old World climbing fern biomass by F. perrepae [123]). Although these results are encouraging, many of these experiments are conducted in the best possible conditions for establishment and rapid buildup of the mite population on plants.…”
Section: Evaluation Of Eriophyid Mite Impact On the Target Weed And Its Implicationsmentioning
confidence: 99%
“…For example, the only feasible way to obtain an impact assessment of A. angustifoliae, although establishment was successful, was to collect data from existing infestations under natural conditions, by comparing branches infested with mites with those that were free of mite attack [121]. This resulted in an estimated 2/3 reduction in seed set on infested branches by not only affecting fruit production directly, but by also reducing the length of fruit bearing branches, further compounding the impact [121]. Although this suggests a high level of impact and will likely slow the invasion potential of Russian olive in North America, there are certain limitations linked to observational data.…”
Section: Evaluation Of Eriophyid Mite Impact On the Target Weed And Its Implicationsmentioning
confidence: 99%